New considerations for SIL verification of functional safety fieldbus communication. (September 2016) - Ding, Long; Wang, Hong; Xu, Aidong; Li, Shixing
Abstract: Safety integrity level (SIL) verification of functional safety fieldbus communication is an essential part of SIL verification of safety instrumented system (SIS), and it requires quantifying residual error probability ( RP ) and residual error rate of function safety communication. The present quantification method of residual error rate uses RP of cyclic redundancy check (CRC) to approximately replace the total RP of functional safety communication. Since CRC only detects data integrity-related errors and CRC has intrinsically undetected error, some other residual errors are not being considered. This research found some residual errors of the present quantification method. Then, this research presents an extended new approach, which takes the found residual errors into account to determine more comprehensive and reasonable RP and residual error rate. From perspective of the composition of safety message, this research studies RP s of those controlling segments (sequence number, time expectation, etc.) to cover the found residual errors beyond CRC detection coverage, and the influences of insertion/masquerade errors and time window on RP are investigated. The results turn out these residual errors, especially insertion/masquerade errors, may have a great influence on quantification of residual error rate and SIL verification of functional safety communication, and they should be treated seriously. Highlights: This paper found some residual errors of the present quantification method. This paper combines diverse safety measures to quantify residual error probability. Insertion/masquerade errors and time window errors are taken into account. Effects of insertion/masquerade errors and time window are discussed. Results obtained are more comprehensive and reasonable than present method.